Hypoattenuated leaflet thickening is associated with silent brain injury. (3rd October 2022) - Nagy, A I; Bartykowszki, A; Apor, A; Suhai, F; Varga, A; Manouras, A; Szilveszter, B; Panajotu, A; Jermendy, A; Turani, M; Molnar, L; Papp, R; et al.
Abstract: Background: The association between hypoattenuated leaflet thickening (HALT) following transcatheter aortic valve implantation (TAVI) and stroke remains contradictory. Whether HALT carries an increased risk of subclinical brain injury (SBI) has not been investigated. Purpose: We investigated whether HALT is associated with SBI on MRI. Furthermore, we assessed whether post-TAVR SBI impacts the patients' cognition and outcome. Methods: 153 patients undergoing TAVR were prospectively enrolled. Brain MRI was performed shortly post-TAVR and 6 months (6M) later to assess the occurrence of acute silent cerebral ischaemic lesions (SCIL) and chronic white matter hyperintensities (WMH). HALT was screened by cardiac CT angiography 6M post-TAVR. Neurocognitive evaluation was performed before, shortly after and 6M following TAVR. Results: At 6M, 115 patients had diagnostic CTA and 10 had HALT. HALT status, baseline and follow-up MRIs were available in 91 cases. At 6M, new SCIL was evident in 16%, new WMH in 66%. New WMH was more frequent (100% vs 62%; p=0.047) with higher median volume (319 vs 50 mm 3 ; p=0.039) among HALT-patients. In uni- and multivariate analysis, HALT was associated with new WMH volume (beta: 0.72; 95% CI: 0.2–1.39; p=0.009). The patients' cognitive trajectory from pre-TAVR to 6M showed significant association with the 6M SCIL volume (beta: −4.69; 95% CI: −9.13 to −027; p=0.038), but was not related to the presence or volume of new WMH. During a 3.1-year follow-up neither HALT, nor the related WMH burden was related with increased mortality (HALT HR: 0.86, 95% CI: 0, 202–3, 687; p=0.84; new WMH HR: 1.09; 95% CI: 0, 701–1, 680; p=0.71). Conclusions: 6M post-TAVR, HALT was linked with greater WMH burden, but did not carry an increased risk of cognitive decline or mortality over a 3.1-year follow-up. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): János Bolyai Scholarship of the Hungarian Academy of Sciences